Associative-verbal field of the concept as a marker of national linguistic consciousness - Pedchenko, Liudmyla (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
The article is devoted to the problem of the universal and national-specific in the linguistic consciousness of representatives of different ethnic groups. The purpose of the study is to identify common features and national specificity of the linguistic consciousness of Ukrainians, Russians and Bulgarians on the basis of a comparative analysis of the semantic structure of the associative-verbal field "people", which objectifies an important linguocultural concept for the Ukrainian, Russian and Bulgarian worldviews. The relevance of the work is due to the significance of the comparative study of associative-verbal fields in the context of the actualization of the intercultural aspect of the study of concepts, national linguistic consciousness and linguoculture in general, which is characteristic of modern anthropocentric linguistics. The empirical basis of the work was the data of the “Slavic Associative Dictionary”, created based on the results of free associative experiments conducted with speakers of four Slavic languages (Russian, Ukrainian, Belarusian and Bulgarian) in the late 1990s. As a result of the study, it was found that associative-verbal fields reveal many common features in the interpretation of the concept of “people” by the linguistic consciousness of Ukrainians, Russians and Bulgarians. Thus, the core of the concept is formed by the cognitive features of “people, crowd”, “number”, national and state-political characteristics, although the place of these features in the nuclear zone of the concept within the national linguistic cultures is different (in Ukrainian the national aspect dominates, in Russian and Bulgarian – the features of “crowd”, “people”). To varying degrees, the ideas of power and greatness, unity, suffering and humiliation are actualized in the structure of the concept. The evaluative zone of the concept in all three languages is ambivalent. However, a comparative analysis of associative fields has also revealed a significant number of national-specific reactions to the stimulus "people". Thus, the cultural and historical features, national-mental differences of the three Slavic peoples determine the specificity of their linguistic consciousness, which is reflected in the structure and specific content of the corresponding associative-verbal fields at the level of both the nuclear zone of the concept and its periphery.